1990
DOI: 10.1212/wnl.40.8.1231
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a defect in NADH

Abstract: We evaluated electron transport chain activity in platelet mitochondria taken from HD patients. All 5 patients studied had striking depressions of NADH:ubiquinone oxidoreductase activity (complex I) (5.36 +/- 2.91 nmol/min/mg; control mean, 19.12 +/- 5.64 nmol/min/mg). Other electron transport chain activities were not significantly different from control values. HD may be caused by a mutation in 1 of the nuclear coded subunits of NADH:ubiquinone oxidoreductase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
92
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(94 citation statements)
references
References 0 publications
2
92
0
Order By: Relevance
“…Mitochondrial dysfunction is considered a common feature in the pathogenesis of neurodegenerative disorders like HD (Kim et al, 2010;Oliveira, 2010;Parker et al, 1990). Mitochondrial dysfunction constitutes a cellular hallmark for neurodegeneration and occurs as a consequence of defective mitochondrial composition, trafficking to synapses, calcium handling, ATP production, transcription abnormalities and/or ETC impairment (Rosenstock et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial dysfunction is considered a common feature in the pathogenesis of neurodegenerative disorders like HD (Kim et al, 2010;Oliveira, 2010;Parker et al, 1990). Mitochondrial dysfunction constitutes a cellular hallmark for neurodegeneration and occurs as a consequence of defective mitochondrial composition, trafficking to synapses, calcium handling, ATP production, transcription abnormalities and/or ETC impairment (Rosenstock et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In platelets from HD patients, some authors found a decrease in complex I activity (Parker et al, 1990), whereas others reported no changes in the activity of mitochondrial complexes (Gu et al, 1996;Powers et al, 2007a). Moreover, the phosphocreatine/ inorganic phosphate ratio was significantly decreased in resting muscle (Koroshetz et al, 1997) of HD patients, evidencing bioenergetic changes in HD peripheral tissues.…”
Section: Introductionmentioning
confidence: 96%
“…Some factors contributing to AD include ␤-amyloid precursor protein (APP) mutations, ApoE genotype, transmembrane proteins S182 and STM2, reduced glucose transport, excitotoxins, head trauma, and deficiencies in mitochondrial cytochrome c oxidase (COX or complex IV) activity (Parker et al, 1990b(Parker et al, , 1994aParker, 1991;Chandrasekaran et al, 1992;Kish et al, 1992;Mutisya et al, 1994;Mattson, 1995;Yanker, 1996;Davis et al, 1997). The idea of a mitochondrial component to neurodegenerative diseases is not new, and it has also been proposed for Parkinson's disease and Guam Parkinsonism / Dementia Complex (Parker et al, 1990a(Parker et al, , 1994aBeal, 1995). The complex IV lesion resembles other electron transport chain (ETC) defects known to produce Leber's neuropathy and neuropathy-ataxia-retinitis pigmentosa (Singh et al, 1989;Goto et al, 1990;Shoffner et al, 1990;Howell et al, 1991;Ortiz et al, 1993).…”
mentioning
confidence: 99%
“…4, 1992 indirectly, by promoting the recycling of vitamin E (Booth et aI., 1982;Landi et aI., 1984;Frey et aI., 1990;Packer et aI., 199 1). The activity of NADH:u biquinone oxidoreductase (complex I) is reduced in Huntington disease (Parker et al, 1990), where en dogenous excitotoxins are responsible for the wide spread damage of striatal neurons (reviewed in Choi, 1988;Young et aI., 1988). Hence, ubiquinone has a potential interest as a protective agent against excitotoxin-induced neuronal degeneration.…”
Section: Discussionmentioning
confidence: 99%